Impact of Brainstorming Method in Developing Speaking skills in Arabic among Level I Female Students at the University of Science and Technology, Sana'a- Yemen - Al -Tair, Ahmed Mohamed Abdel Rahman (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the impact of using the brainstorming method in developing speaking skills in Arabic among Level I university female students. To achieve this, the excremental method was used. The study sample consisted of level I students of Laboratories, Faculty of Medicine, University of Science and Technology- Sana'a. The students were divided into an experimental and a control group, and a learning material, consisting of three modules, was specially designed for them. Also, an achievement test, which was checked for validity and reliability, was also administered to both groups after the learning material was used. The experimental group was taught by the brainstorming method, whereas the control group was taught by the lecturing method. Data was analyzed using means, standard deviation and t-test. Major findings revealed that the experimental group that was taught by the brainstorming method surpassed the control group that was taught by the lecturing method. It was recommended that there is a need to use the brainstorming method in teaching as it proved to be better than the lecturing method.
Keywords: brainstorming; Arabic speaking skills